Pengaruh Harga, Promosi, dan Kualitas Pelayanan terhadap Kepuasan Konsumen dalam Menggunakan Jasa Sewa iPhone by Alfa Kamera Madiun - Rahma Julita Kusuma Ningrum; Tatik Mulyati; Hartirini Warnaningtyas (Student Scientific Creativity Journal, 2026)
The rapid advancement of information and communication technology has positioned smartphones as an essential tool to support productivity in the creative industry. Apple’s iPhone is highly demanded due to its superior camera quality and high prestige, yet its expensive price makes it inaccessible to all segments. This limitation creates a lucrative market for iPhone rental services. This study aims to analyze the partially and simultaneously influence of price, promotion, and service quality on customer satisfaction among users of iPhone rental services by Alfa Kamera Madiun, as well as to determine the most dominant factor. This research employs a quantitative method with an associative causal design. The population consists of consumers who have rented an iPhone from Alfa Kamera Madiun, with a sample size of 232 respondents selected through purposive sampling. Data collection was carried out using a Likert-scale questionnaire. The data analysis technique utilized multiple linear regression analysis with JASP software assistance. The results indicate that price, promotion, and service quality have positive and significant effects on customer satisfaction, both partially and simultaneously. Furthermore, service quality emerged as the most dominant factor affecting customer satisfaction. These findings suggest that the management needs to continuously enhance their service delivery alongside competitive pricing and creative promotions to secure customer retention amid rising market competition.